2015
DOI: 10.1007/7854_2015_5011
|View full text |Cite
|
Sign up to set email alerts
|

Affective Biases in Humans and Animals

Abstract: Depression is one of the most common but poorly understood psychiatric conditions. Although drug treatments and psychological therapies are effective in some patients, many do not achieve full remission and some patients receive no apparent benefit. Developing new improved treatments requires a better understanding of the aetiology of symptoms and evaluation of novel therapeutic targets in pre-clinical studies. Recent developments in our understanding of the basic cognitive processes that may contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 121 publications
0
35
0
Order By: Relevance
“…Recently, studies suggest that drugs such as tetrabenazine and varenicline may exacerbate depressive symptoms in patients with a pre‐existing psychiatric illness (Kenney et al, ; Thomas et al, ). Considering the hypothesis that negative affective biases play a key role in the development of persistent negative mood states (Harmer et al, ; Robinson and Roiser, ), it is plausible that an increased sensitivity to negative affective bias may underlie individual vulnerability to drug‐induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies suggest that drugs such as tetrabenazine and varenicline may exacerbate depressive symptoms in patients with a pre‐existing psychiatric illness (Kenney et al, ; Thomas et al, ). Considering the hypothesis that negative affective biases play a key role in the development of persistent negative mood states (Harmer et al, ; Robinson and Roiser, ), it is plausible that an increased sensitivity to negative affective bias may underlie individual vulnerability to drug‐induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…Negative bias in emotional processing seen in depression has been reliably demonstrated across domains of emotional cognitive processing, including perception, attention, memory, and reward (Roiser et al 2012, Roiser and Sahakian 2013, Robinson and Roiser 2016. For example, people with depression are more likely to perceive and categorize ambiguous facial expressions as negative in the Facial Emotions Recognition Test (FERT); they show preferential memory for negative emotional information in emotional word-based memory encoding (ECAT) and immediate and delayed recall (EREC) tasks; take longer to name the colour of negative emotional words in the emotional Stroop task (i.e.…”
Section: The Cognitive Neuropsychological Hypothesis Of Antidepressanmentioning
confidence: 99%
“…The findings reported here provide important information for comprehension of cognition, as evidence is presented for a role for the ANS in cortical auditory processing, which is relevant for communication and social behavior [1,2]. In this study, mechanisms of cortical auditory processing were revealed to be associated with the parasympathetic control of HR and sympathovagal balance.…”
Section: Discussionmentioning
confidence: 52%
“…To provide details regarding the relationship between central auditory processing and the ANS, this study investigated the association between CAEP components and resting time and frequency domain indices of HRV. The following outcomes are highlighted: (1) There was significant association of the vagal component of HR control and sympathovagal balance at rest with the N2 and P2 waves; (2) This association only occurred in the left ear, indicating involvement of the right cortical hemisphere; and (3) The hypothesis is proposed that the autonomic component of heart rhythm interacts with cortical sound processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation